Performance of tau-lepton reconstruction and identification in CMS - Chatrchyan, S. (2012)
The performance of tau-lepton reconstruction and identification algorithms is studied using a data sample of proton-proton collisions at root s = 7 TeV, corresponding to an integrated luminosity of 36 pb(-1) collected with the CMS detector at the LHC. The tau leptons that decay into one or three charged hadrons, zero or more short-lived neutral hadrons, and a neutrino are identified using final-state particles reconstructed in the CMS tracker and electromagnetic calorimeter. The reconstruction efficiency of the algorithms is measured using tau leptons produced in Z-boson decays. The tau-lepton misidentification rates for jets and electrons are determined.